2022
DOI: 10.3390/w14193061
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Modeling and Optimization of Process Parameters for 2,4-Dichlorophenoxyacetic Acid Removal by Using AC/PDMAEMA Hydrogel Adsorbent: Comparison of Different RSM Designs and ANN Training Methods

Abstract: In this study, the response surface methodology (RSM) and artificial neural network (ANN) were employed to study the adsorption process of 2,4-dichlorophenoxyacetic acid (2,4-D) by using modified hydrogel, i.e., activated carbon poly(dimethylaminoethyl methacrylate) (AC/PDMAEMA hydrogel). The effect of pH, the initial concentration of 2,4-D and the activated carbon content on the removal of 2,4-D and adsorption capacity were investigated through the face-centered composite design (FCCD), optimal design and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The fit of the model for the responses is determined by the coefficient of determination (R 2 ) and the coefficient of variation (C.V) values; the value of R 2 must be greater than 0.8 to indicate a good model for the data [62]. The C.V is the standard deviation-tomean ratio, expressed as a percentage (%); C.V less than 10% indicates that the model is reproducible [63][64][65]. In this study, all the responses had an R 2 greater than 0.90; as shown in Table 5, the R 2 for O&G and COD was 98.38% and 95.58%, respectively.…”
Section: Statistical Analysis By Rsmmentioning
confidence: 99%
“…The fit of the model for the responses is determined by the coefficient of determination (R 2 ) and the coefficient of variation (C.V) values; the value of R 2 must be greater than 0.8 to indicate a good model for the data [62]. The C.V is the standard deviation-tomean ratio, expressed as a percentage (%); C.V less than 10% indicates that the model is reproducible [63][64][65]. In this study, all the responses had an R 2 greater than 0.90; as shown in Table 5, the R 2 for O&G and COD was 98.38% and 95.58%, respectively.…”
Section: Statistical Analysis By Rsmmentioning
confidence: 99%
“…Sridevi et al [45] employed an FFNN model to predict the adsorption of 2,4-D onto AC generated from Ulva prolifera biomass, and they recorded an R 2 = 0.96 and an RMSE = 0.1007. Dahlan et al [46] used an FFNN to model the adsorption process of 2,4-D onto a modified hydrogel using three input layers; the model complexity was substantially reduced, and they found high accuracy (R 2 = 0.99 and RMSE = 0.0004). Isiyaka et al [47] reported the use of an FFNN model to predict the remediation of MCPA in an aqueous medium using an aluminum-based metal-organic framework and recorded high accuracy (R 2 = 0.99 and RMSE = 0.0040).…”
Section: Influence Of Operational Variablesmentioning
confidence: 99%
“…Sridevi et al [45] employed an FFNN model t predict the adsorption of 2,4-D onto AC generated from Ulva prolifera biomass, and the recorded an R 2 = 0.96 and an RMSE = 0.1007. Dahlan et al [46] used an FFNN to model th…”
Section: Influence Of Operational Variablesmentioning
confidence: 99%